Assessing strabismus in children. Issue 1 (January 2020) - Bommireddy, Tejaswi; Taylor, Kate; Clarke, Michael Patrick
Abstract: Strabismus, also known as a squint, is an ocular misalignment. In the UK the prevalence of strabismus in children is 2.1%. There are multiple causes of strabismus in children; some of which can be sinister and are potentially eye or life threatening. Therefore it is essential that strabismus is identified and managed appropriately and in a timely manner. Amblyopia is frequently associated with strabismus, and can be a cause or a complication of strabismus, it needs to be recognized and treated early to prevent a permanent reduction in visual acuity. This article explains how to correctly assess strabismus in children. A detailed history should be taken, and an ocular examination should be performed using the correct techniques and ocular motility tests. The important red flag features of strabismus in children are also outlined in this article.